Documents on Survey Analysis - Seetharama, S. (Journal of Information and Knowledge, 1972)
Presents data regarding the period-wise distribution, scatter and seepage of documents on Survey Analysis. 33 periodicals carry nearly 70 per cent of the documents. The pattern of occurrence of articles in periodicals follows Bradford’s law of scattering. Details regarding the host periodicals on Survey Analysis - such as country of origin, sponsors, language - are briefly discussed.